CELL VOLUME CONFERENCES - V. Štrbák (Бюллетень сибирской медицины, 2013)
This mini-review describes the history of cell volume conferences with the emphasis on the research of cell volume sensitive peptide exocytosis initiated by Prof. Monte A. Greer as well as the recent achievements on the study of the mechanisms of cell volume adjustment and their implications in the regulation of metabolism, gene expression, cell proliferation and death.